Religiões brasileiras de matrizes africanas no contexto da Lei 10.639/03 em Cuiabá-MT - Vieira, Maurício Benedito da Silva (2016)
The constant attacks and disrespect directed at Terreiros of Candomblé and Umbanda, as well as their supporters, raise a question quite particular: how the school has been articulated to contribute to the minimization of religious intolerance? It's been 13 years of implementation of the Federal Law 10.639 / 03 and the school as address issues related to African culture and african-Brazilian its symbolism? These are questions that guide this research. It can be considered the implementation of Law 10.639 / 03 as a strategy for the education of their contribution to the elimination of racism and intolerance to religions of African origin in Brazilian society. This research seeks to analyze the level of involvement, interest and possible rejections of basic education teachers of the Municipal Cuiabá, concerning the development of the contents of the Brazilian religions of African origin and the application of these in the classroom, considering the implementation of Law 10.639 / 03. This is a qualitative research on the macro perspective (Brandao 2001). We used survey form type, such as data collection instrument was answered by teachers. Participate in this research professors of the Municipal Cuiaba, loaded in 11 school units, two of which are located in rural areas and nine in the urban area, all located near Terreiros Umbanda and / or Candomble. Through the survey, teachers reveal issues that gain centrality in the course of research, particularly by showing feelings of religious intolerance. They are arguments that present the reality of "ground school" and pointing to the tense relationship between the couple when the reference in question is the religious orientation. The survey reveals that among the teachers there is resistance as the approach of related content Brazilian religions of African origin, and in some cases some teachers have strong resistance negatively characterizing the practices linked to Candomblé and Umbanda.